The effects of Lepidium meyenii on MSG-induced subfertility in male Wistar rats: Targeting oxidative stress, pro-inflammatory cytokines, steroidogenic enzymes, and reproductive hormones regulation - Temidayo S. Omolaoye; Surendra Singh Rawat; Naglaa Gamil Shehab; Eslam El Nebrisi; Stefan S. Du Plessis (Heliyon)
Objective and rationale: Although monosodium glutamate (MSG), commonly used to enrich food flavour, is generally considered safe for consumption, evidence has shown its adverse effects on physiological functions, including male reproduction, when consumed excessively. Lepidium meyenii (Maca), on the other hand, a plant belonging to the Brassicaceae family, has been shown to have diverse health benefits. The current study investigated pathways through which MSG could induce subfertility, and whether treatment with Maca root extract would proffer amelioration via those routes. Methods: Eighteen male Wistar rats were randomly divided into three groups. Animals were orally (oral gavage) administered MSG (900 mg/kg/day for 45days), MSG and Maca (900 mg/kg/day of MSG and 500 mg/kg/day of black Lepidium meyenii root extract), or water only (control group), for a total period of 80 days. MSG was administered for the first 45 days, followed by Maca or water for the subsequent 35 days. Spermatozoa were collected from the caudal epididymis for sperm assessments. The testis and prostate were used for biochemical assays and immunofluorescent localization of biomarkers of interest. Results: MSG administration significantly reduced total and progressive sperm motility (p < 0.05), decreased total antioxidant capacity (TAC) (p < 0.001), increased mRNA expression of TNF-α, IL-6, IL-1β in the testis and prostate (p < 0.05), protein expression of GP130 in the testis, reduced serum testosterone, and altered expression of steroidogenic markers. These adverse effects were mildly ameliorated upon treatment with Maca. Conclusion: Findings highlights how MSG could cause male reproductive dysfunction via reduction of TAC, increase in pro-inflammatory cytokines, alter reproductive hormones and reduced protein expression of steroidogenic markers. Treatment with Maca significantly improved sperm motility, possibly by enhancing TAC levels and reducing proinflammatory cytokines. However, this hypothesis needs further investigation.